The Evaluation of Pancasila Student Profile Strengthening Project Using the Kirkpatrict Model at SMAN 2 Tanggul - Budi Muttaqin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to evaluate the implementation of Pancasila student profile strengthening project at SMAN Tanggul in academic year 2022/2023. The research method used is a qualitative approach with the Kirkpatrick evaluation model which includes reaction, learning, behavior, and result. Data were obtained through interviews and observations with data sources of 10 student, school principal, and 12 teachers. Data analysis techniques used include data collection, data reduction, data display, and conclusion drawing/verification. The data validity techniques used are extension of participation, persistence of observation, and triangulation. The results of this study indicate that the project activities of pancasila student profile strengthening project at SMAN 2 Tanggul have a very positive impact on character development, skills, and creativity in students. However, in the future the school must make improvements and developments in terms of human resources, the stability of the project design, facilities, and a clear budget so that the implementation of the project can be maximized